Clinicopathologic associations of BRAF mutation status in patients with metastatic melanoma - Kwapisz, Dorota; Dansonka-Mieszkowska, Agnieszka; Switaj, Tomasz; Falkowski, Slawomir; Rutkowski, Piotr (European Journal of Oncology and Environmental Health, 2016)
Aim: BRAF is frequently mutated in cutaneous melanoma. The aim of the study was to assess BRAF status association with clinicopathologic features and outcome in patients with metastatic melanoma. Methods: We identified 197 consecutive Polish patients with metastatic melanoma treated in one oncological center and tested for BRAF mutation. We performed a retrospective chart review of patients to identify clinicopathologic characteristics in BRAF-mutant and BRAF wild-type patients. Results: 122/197 patients (61.9%) had BRAF mutation. The age at diagnosis of primary melanoma (PM) was significantly younger for BRAF-mutant (median age 52, n=122, range 19−78) than for BRAF wild-type (median age 58, n=75, range 19-85; p<0.05) patients. The most common site of PM in BRAF-mutant patients was the trunk (45.9%). The most common locations of first distant metastasis were the lungs, regardless of the BRAF mutation status. There was no difference in the time to occurrence of metastatic disease between BRAF-positive and BRAF-negative cohorts (p=0.75). Patients without BRAF mutations had non-significantly better overall survival (OS) when calculated from diagnosis of metastatic disease as compared to BRAF-mutant patients not treated with tyrosine kinase inhibitors (median OS: 337 vs. 270 days, respectively), but OS was significantly better for BRAF-mutant patients treated with BRAF/MEK inhibitors (median OS not reached; p<0.05). Conclusions: Age at diagnosis differed between the groups. The presence of mutant BRAF had no impact on the interval from diagnosis of melanoma to first distant metastasis, but had some impact on the natural course of metastatic disease.